A Cloud-based Digital Twin Manufacturing System based on an Interoperable Data Schema for Smart Manufacturing. Issue 12 (1st December 2020) - Park, Yangho; Woo, Jungyub; Choi, SangSu
ABSTRACT: The worldwide manufacturing industry is facing a wide range of changes. Examples include the diversification of customer demands, increases in labor costs and energy resource costs, environmental pollution, and growth uncertainty. Based on the experience of advanced countries and global manufacturers, smart manufacturing systems (SMS) have the potential to address these. SMS can connect raw materials, production systems, logistic companies, and maintenance schedules using the capabilities of industrial, internet of things (IoT). These connections are creating cyber-physical production systems (CPPS) and linking functions across the entire product lifecycle. These connections are possible today because of the advances in digital manufacturing (DM) technologies that can facilitate factory design, redesign, and analysis in CPPS and help to continuously and efficiently manage factory performance optimization. However, implementing DM today, especially in SMEs, is difficult because the required interface standards and data schema do not exist – unlike other technologies and system such as CAD, PLM, MES, and SCM. This paper describes an approach to design and develop such a data schema based on a reference activity model developed by NIST. The paper then develops a cloud-based DM system based on the data schema. Lastly, its application cases are described, and application effects are discussed.